FDM-3D printing LLDPE/BN@GNPs composites with double network structures for high-efficiency thermal conductivity and electromagnetic interference shielding. (15th February 2023) - Peng, Zilin; Lv, Qinniu; Jing, Jingjing; Pei, Haoran; Chen, Yinghong; Ivanov, Evgeni
Abstract: Towards the high-frequency and miniaturization of modern electronic devices, the multi-functional materials with high-efficiency thermal management and electromagnetic interference shielding performance are urgently demanded. The contributions in materials are mostly focused on a single function, and difficult to meet the requirement of the precision device with complicated structures. Herein, linear low-density polyethylene (LLDPE)/boron nitride (BN)@graphene nanoplatelets (GNPs) composite parts with double network structures were designed and realized by combining ball-milling strategy and fused deposition modeling (FDM) 3D printing technology. The FDM-3D printed parts could exhibit a thermal conductivity of 3.11 W/(m·K) along the printing direction at 3.51 vol% GNPs loading, achieving an improvement of ∼2.88 and ∼8.33 times over that of flat printing parts and pure LLDPE, respectively. The long-range aligned network along the printing direction is formed due to the shear extrusion effect during FDM-3D printing. Also, FDM-3D printing is applied to print heat sinks with excellent thermal conductive property in vertical direction. Furthermore, the ball milling process could enable the GNPs to form thermal and electrical conductivity pathways in LLDPE/BN composites. The printed parts accordingly exhibit good electromagnetic shielding performance (27.8 dB) and electrical conductivity (12.5 S/m). This study not only enriches the strategy for preparation of multifunctional FDM 3D printed parts, but also paves the way for further applications in advanced thermal management and protection against electromagnetic irradiation. Graphical abstract: Image 1 Highlights: The LLDPE/BN@GNPs double conductive network was successfully built by combining ball milling and FDM-3D printing technologies. The FDM-3D printed parts of LLDPE/BN@GNPs composites possess excellent thermal conductivity and good EMI shielding property. The high-performance heat sinks were made by adopting FDM alignment strategy and successfully attempted in thermal management. The constructed GNPs networks endow FDM-3D printed parts with high electrical conductivity and efficient EMI shielding property.